Gestão de resíduos sólidos: um estudo da conscientização ambiental em uma cidade do Brasil - Santos, Esmeraldo Macêdo dos (2002)
The present study inserts on the international environmental thematic, approaching the integrated management of solid waste and the participation of the social actors in the search of the sustainable development. The awareness in combining it still describes a Selective Collection Program SCP of solid waste, in partnership with the municipal public power, in the development of joint actions that result in better alternatives of waste management in the urban centers, providing better life quality for the population and conservation of the environment. The aim of this research is to study problematic of the management of solid waste under the point of view of the environmental awareness and the participation of the population in a city of Brazil. In this matter, the target of the work is focusing on the strategy of solid waste management, through the attitudes and the respondents behaviors to aid in the making decision of the public manager related to the implantation of a selective collection program in Natal/RN. The methodology used in this work constitutes in the application of a questionnaire with scales of the type Likert being constituted of variables that compose the aspects of attitudes and of behaviors, besides a social-demographic scale. For analysis statistics is used the Pearson s Chi-Square Method in order to verify the dependence of the associations between the social-demographic variables and the attitude and the behavior ones. The results appear for a larger participation in a SCP, since this provides a better quality of life of the population (28,3 %), followed for offering a financial advantage (27,3%). Other results indicate the existence of the variables that exercise influence on the environmental awareness of the population to its demographic aspects